Job, Family and Individual Factors as Predictors of Work-Family Conflict - Ahmad, Aminah (2008)
The growing interest in understanding fully the interface of work and family roles and their antecedents has stimulated the development of a predictive model of work-family conflict. A model is developed on predictors of work-family conflict which suggests that the predictors could be job-related (job type, work time commitment, job involvement, role overload, job flexibility), family-related (number of children, life-cycle stage, family involvement, child care arrangements) and individual-related (life role values, gender role orientation, locus of control, perfectionism). This present model is based on the stress-strain model (Dunham, 1984) whereby the predictors are referred to as stressors, and the conflict as strain.